Naturalizing the essential tension. - D’Agostino, Fred (Synthese, 2008)
Kuhn’s “essential tension” between conservative and innovative imperatives in enquiry has an empirical analogue—between the potential benefits of collectivization of enquiry and the social dynamic impediments to effective sharing of information and insights in collective settings. A range of empirical materials from social psychology and organization theory are considered which bear on the issue of balancing these opposing forces and an institution is described in which they are balanced in a way which is appropriate for collective knowledge production.